Adding 'iterativity' to the credibility, relevance, legitimacy: A novel scheme to highlight dynamic aspects of science–policy interfaces. Issue 54 (December 2015) - Sarkki, Simo; Tinch, Rob; Niemelä, Jari; Heink, Ulrich; Waylen, Kerry; Timaeus, Johannes; Young, Juliette; Watt, Allan; Neßhöver, Carsten; van den Hove, Sybille
Highlights: Credibility, relevance and legitimacy (CRELE) help to understand science–policy interfaces (SPIs). SPIs are usually continuous interaction processes with strong dynamic features. Iterativity complements CRELE attributes through focus on dynamic interactions. We identify 14 SPI design features that influence CRELE and iterativity. Abstract: Credibility, relevance and legitimacy (CRELE) of knowledge are widely recognized as key attributes of effective science–policy interfaces (SPIs). Yet, notwithstanding efforts to enhance the CRELE attributes of an SPI, it may still lack impact or be dismissed as not being credible, legitimate or relevant both inside, and outside the SPI. We introduce 'iterativity' as an additional attribute to the CRELE framework to better capture dynamic, continuous and multi-directional interactions between science, policy and society related to SPIs. Iterativity is understood in the context of an important shift in perspective by which SPIs are viewed as dynamic, evolving processes rather than linear processes or isolated events. Based on empirical material on biodiversity-related SPIs, we identify 14 features and lessons learned that explain the outcomes of SPIs regarding their participants and external audiences, and examine how SPIs' structures, objectives, processes and outputs help to build CRELE and iterativity (CRELE + IT). The four attributes of CRELE + IT and results related to the features explaining outcomes of SPIs also provide useful practical tools for the design, implementation and revision of effective science–policy interfaces. These lessons regarding CRELE + IT help us understand both when and why SPIs are able to contribute to the pressing social and ecological need to halt biodiversity loss and the further deterioration of ecosystem services.